INTEGRASI ZAKAT DAN PAJAK DI INDONESIA DALAM TINJAUAN HUKUM POSITIF DAN HUKUM ISLAM - Masnun Tahir (Al 'Adalah: Jurnal Hukum Islam, 2017)
Abstract: The Integration of Zakat and Taxation in Indonesia in the Views of Positive Law and Islamic Law. This paper propose a concept of integration between taxes and zakat to accelerate the achievement of social welfare in Indonesia. The integration is important as the growth of zakat steadily increases from time to time which is marked by the increasing number of Amil Zakat and alms acquisition from year to year. At the same time, the development of wealth and the service quality of obligatory zakat distributions, including utilization, is also increases progressively. Undoubtly, with this significant growth, charity, like the tax, can be utilized as a tool to achieve social walfare as well as to improve the economy of Indonesia.